Jung - "Storr, Anthony" (Glasgow, 1973)
In this concise introduction, Anthony Stevens explains clearly the basic concepts of Jungian psychology: the collective unconscious, complex, archetype, shadow, persona, anima, animus, and the individuation of the Self. He examines Jung's views on such disparate subjects as myth, religion, alchemy, `sychronicity', and the psychology of gender differences, and he devotes separate chapters to the stages of life, Jung's theory of psychological types, the interpretation of dreams, the practice of Jungian analysis, and to the unjust allegation that Jung was a Nazi sympathizer. Finally, he argues that Jung's visionary powers and profound spirituality have helped many to find an alternative set of values to the arid materialism prevailing in Western society.
Keywords: Psychology